Intravascular ultrasound-supported percutaneous angioplasty of post-kidney transplant renal artery bifurcation stenosis. (February 2022) - Vijayvergiya, Rajesh; Kasinadhuni, Ganesh; Bootla, Dinakar; Rajan, Palanivel; Sharma, Ashish; Lal, Anupam
Background: Transplant renal artery stenosis (TRAS) is an uncommon complication following renal transplantation. Its usual clinical presentation includes worsening hypertension and/or renal function, without any evidence of graft rejection. Bifurcation renal artery stenosis of the transplanted renal artery is rarely encountered. Methods: Percutaneous transluminal renal angioplasty (PTRA) with or without stenting is the procedure of choice to treat TRAS. We hereby describe a patient, who presented with impaired renal functions, four months following the renal transplantation. He underwent intravascular ultrasound-guided PTRA of the bifurcation lesion of TRAS. Results and conclusion: Superior renal artery had coronary drug-eluting stent implantation, while inferior renal artery and side branch of the superior renal artery had balloon angioplasty, alone. Post-intervention, the raised serum creatinine level decreased from 2.9 mg% to 1.7 mg%. The index case described the successful PTRA and stenting of the bifurcation lesion of TRAS, the technical results of which was optimized with the use of intravascular ultrasound.